2014
DOI: 10.1001/jamainternmed.2014.169
|View full text |Cite
|
Sign up to set email alerts
|

Nonleg Venous Thrombosis in Critically Ill Adults

Abstract: ; for the PROTECT (Prophylaxis for Thromboembolism in Critical Care Trial) Investigators, on behalf of the Canadian Critical Care Trials Group and the Australian and New Zealand Intensive Care Society Clinical Trials Group IMPORTANCE Critically ill patients are at risk of venous thrombosis, and therefore guidelines recommend daily thromboprophylaxis. Deep vein thrombosis (DVT) commonly occurs in the lower extremities but can occur in other sites including the head and neck, trunk, and upper extremities. The ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 22 publications
(23 reference statements)
2
42
2
Order By: Relevance
“…7,8 Although the majority of asymptomatic CRT cases remain subclinical, symptomatic DVT occurs in 1%-5% of patients with a CVC (Table 1). [9][10][11][12] A prospective study of 444 cancer patients with a CVC reported symptomatic, ipsilateral DVT in 4% at a median of 30 days after insertion. 13 This corresponds to an incidence of 0.3 per 1000 catheter-days.…”
Section: Incidence Of Crtmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Although the majority of asymptomatic CRT cases remain subclinical, symptomatic DVT occurs in 1%-5% of patients with a CVC (Table 1). [9][10][11][12] A prospective study of 444 cancer patients with a CVC reported symptomatic, ipsilateral DVT in 4% at a median of 30 days after insertion. 13 This corresponds to an incidence of 0.3 per 1000 catheter-days.…”
Section: Incidence Of Crtmentioning
confidence: 99%
“…14 Among 3218 critical care patients randomized to low-dose heparin or low-molecular-weight heparin (LMWH) as thromboprophylaxis, only 1% developed symptomatic catheterrelated DVT during their intensive care unit stay. 12 …”
Section: Incidence Of Crtmentioning
confidence: 99%
“…The κ coefficient of 0.77 is substantial but suboptimal because it is below the κ coefficient of 0.80 typically needed to robustly ascertain the outcome in a randomized control trial [16]. In studies preparatory to a multicenter randomized control trial of thromboprophylaxis in critically ill adults, the concordance between readings using consultative US ranged from 0.29 to 0.71 in the upper extremity veins to 1.00 in the lower extremity veins [19, 20]. We will conduct calibration studies in our multicenter randomized control trial to increase the κ coefficient to at least 0.80 [19].…”
Section: Discussionmentioning
confidence: 99%
“…Thromboses of the limbs may be further classifi ed as proximal or distal and superfi cial or deep [ 13 ]. The location of the venous thrombosis is critically important, particularly in the lower limb, as it determines the therapeutic approach.…”
Section: Site Of Venous Thrombosismentioning
confidence: 99%
“…Line removal was associated with a signifi cantly greater occurrence of clot improvement on the follow up duplex. Lamontague and colleagues screened a cohort of 3,746 medical-surgical ICU patients who were receiving pharmacologic thromboprophylaxis for the presence of non-leg DVT (NLDVT) [ 13 ]. In this study 2.2 % of patients developed one or more NLDVT.…”
Section: Upper Extremity Dvtmentioning
confidence: 99%